Forward and Futures Prices: Evidence from the Foreign Exchange Markets - CORNELL, BRADFORD; REINGANUM, MARC R. (Journal of Finance, 1981)
ABSTRACT Empirical studies of the Treasury Bill markets have revealed substantial differences between the futures price and the implied forward price. These differences have been attributed to taxes, transaction costs, and the settling up procedure employed in the futures market. This paper examines the forward and futures prices in foreign exchange in an attempt to distinguish between the competing explanations.